Air quality assessment in Southeast Brazil during COVID-19 pandemic and lockdown: report of increased air pollution - Bruno Kabke Bainy; Ilma Aparecida Paschoal; Ana Maria Heuminski de Avila; Henrique Oliveira dos Santos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
On March 24, 2020, a partial lockdown was decreed in the state of São Paulo, Brazil, as a measure to hinder the spread of COVID-19, which consisted in prohibiting crowding and advising people to stay home, except for urgent or extremely necessary matters. Based on studies performed in other countries, this study aims to assess the impacts of the lockdown on the air quality of five cities in the state of São Paulo. Our study was conducted by using particulate matter and nitrogen dioxide as air quality indicators, and by correlating the contaminants concentrations with weather data. The results showed an increase in these contaminants in all cities within the first weeks after the lockdown compared with the weeks before the decree and with the same period in previous years. This result is inconsistent with the literature. Therefore, a secondary goal was set to investigate the possible cause (or causes) of such deterioration in air quality, which led to the increased number of wildfires. The anomalous dry weather favored the burning of vegetation in agricultural rural areas and in small, vegetated areas near the municipalities, and limited pollution scavenging by rainfall, both of which contributed to higher pollution concentration. We hypothesize the possible effects of worse air quality on the aggravation of COVID-19, but further research is necessary to obtain a complete assessment.